Real-time and versatile laser-power stabilization with arbitrary amplitude modulation - J. Phrompao (2020)
© Published under licence by IOP Publishing Ltd. We have demonstrated a technique to stabilize laser power at any point in an optical circuit. By employing a self-made Arduino-controlled stabilizer for real-time monitoring and generating feedback signal, the power fuctuation after an acousto-optic modulator (AOM) can be suppressed to 0.16% at an average power of 33.34W. Our arrangement also allows simultaneous amplitude modulation using an arbitrary waveform. The system design and principle of operation are described.